Isola eaudiobook A novel. - Goodman, Allegra (Books on Tape, 2025)
REESE’S BOOK CLUB PICK • “A shocking story, made all the more stunning by the fact that it has its roots in true history.”—Jodi Picoult, author of By Any Other Name “A new generation of survival story . . . an extraordinary book that reads like a thriller, written with the care of the most delicate psychological and historical fiction.”— Vogue (Best of 2025 Preview) A young woman and her lover are marooned on an island in this “lushly painted” ( People ) historical epic of love, faith, and defiance from the bestselling author of Sam . Heir to a fortune, Marguerite is destined for a life of prosperity and gentility. Then she is orphaned, and her guardian—an enigmatic and volatile man—spends her inheritance and insists she accompany him on an expedition to New France. That journey takes a unexpected turn when Marguerite, accused of betrayal, is brutally punished and abandoned on a small island. Once a child of privilege who dressed in gowns and laced pearls in her hair, Marguerite finds herself at the mercy of nature. As the weather turns, blanketing the island in ice, she discovers a faith she’d never before needed. Inspired by the real life of a sixteenth-century heroine, Isola is the timeless story of a woman fighting for survival. *This audiobook contains a PDF with a map and recommendations for further reading from the book.